Hygienic – sanitary quality and food manufacturing practices in a student cafeteria in Mexico - Almeida-Perales, Cristina; Ruiz de Chávez-Ramírez, Dellanira; Valdez-Hibel, Angélica (Universidad y Salud, 2024)
Introduction: Adherence to official health standards is essential to prevent human health risks. Objective: To assess the hygienic-sanitary quality and good food manufacturing practices (GMP) in a student cafeteria in Mexico. Materials and methods: Quasi-experimental and analytical study. During 2020, bacteriological tests were carried out on samples taken from food, water, surfaces, and hands of food handlers. In addition, GMP were evaluated. Based on the current Mexican official health regulations, 57 samples were collected to isolate and identify pathogens. GMP were assessed in 20 food handlers before and after a 10-week training intervention and a test was used with α=0.05. Results: More than 50% of samples were found to have microorganisms associated with health risks, including Escherichia coli, Staphylococcus aureus, Pseudomonas, Acinetobacter baumanni complex and total coliforms. The analyses before and after the GMP training intervention showed statistically significant differences in terms of the presence of these pathogens (p≤0.05). Conclusions: The hygienic-sanitary quality of the analyzed cafeteria turned out to be a risk for the health of students, which was related to the first assessment of GMP in food handlers. Consequently, the results improved after the intervention.